Four-way decomposition of the effects of nutrient supplement and physical exercise on depression among older Chinese: a nationwide cross-sectional analysis - Huang, Shuna; Guo, Jianhui; Jiang, Renquan; Ma, Ke; Lin, Fuxin; Li, Huangyuan; Kang, Dezhi; Wu, Siying (BMC public health, 2024)
Studies on the associations between nutrient supplement, physical exercise, and depression among persons 65 years and older in China are still lacking. We aimed to investigate the association between nutrient supplement and depression and to explore the role of physical exercise in this association. A total of 8,427 older Chinese adults from the Chinese Longitudinal Healthy Longevity Survey were included in this study. The Center for Epidemiologic Studies Depression Scale was used to assess participants' depression, and nutrient supplement and physical exercise were evaluated using self-reports. Linear regression and logistic regression were performed to explore the association between nutrient supplement and depression, and a four-way decomposition method was used to explore the effects of nutrient supplement and physical exercise on depression. A total of 26.2% of participants suffered from depression. Prior to decomposition, multivariable linear regression and logistic regression models showed that older adults who received nutrient supplement had lower depression score (β: -0.704; 95% confidence interval [CI]: -1.004, -0.404) and a lower risk of depression (odds ratio: 0.710; 95% CI: 0.564, 0.894), especially for calcium and multivitamins. Four-way decomposition analysis suggested that physical exercise mediated the associations between nutrient (protein, calcium, iron, zinc, multivitamins, vitamin A/D, docosahexaenoic acid, and others) supplement and depression (all P < 0.05). Calcium or multivitamin supplements were associated with inverse depression, and the reason why this association existed could be partly explained by the mediating effect of physical exercise.